Flood of 1954: The Beginning of a Developmental State - Ghimire, Sharad (New Angle: Nepal Journal of Social Science and Public Policy, 2014)
Development projects evolve with reference to particular framings of the need and imperatives of developing country. Once development projects get legitimated in this way, the aid agencies deepen their presence to move in a direction of their choice. This is evident from an examination of the 1954 flood in Nepal which devastated a significant part of the hills and Tarai in the eastern, central and western areas. This paper looks into the disaster caused by that flood; into how the government of Nepal, the civil society and donors responded to it; and into the way the crisis stirred conflict and contestation among political parties within and outside the government. This paper is based primarily on the review of newspaper coverage around the flood, the political processes and the inauguration of development project in Nepal in the 1950s. It shows the extraordinary power of how the crisis caused by flood stirs up political contestation and helps legitimize actions of one or the other actor, including the donors. These insights on the power of a big disaster to command response from a wide range of domestic actors and donors help us question the largely technocratic framing of the ongoing debate around disaster risk reduction.